Polylactic acid fluffy nano fiber membrane capable of efficiently filtering out gas and particulate matters and preparation method of polylactic acid fluffy nano fiber membrane

By adding SC crystals to the polylactic acid fiber membrane and synthesizing MOF-type nanocrystals in situ, MOF-type SC crystal electret polylactic acid fluffy nanofiber membrane is formed, which solves the filtration and adsorption of air particles and toxic gases, and achieves high efficiency , low resistance air purification and gas capture effects.

CN119455682AActive Publication Date: 2025-02-18SHENHUA SHENDONG COAL GRP +3
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411591366.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problems of air particulate pollution and toxic gas hazards, especially in the efficient filtration of gases and particulate matter.

Method used

By preparing SC crystals and adding them as electrets to polylactic acid fibers, the interface polarization of the fiber membrane is improved, and MOF-type nanocrystals are synthesized in situ on the fiber surface to form MOF-shaped SC crystal electret polylactic acid fluffy nanofibers membrane.

Benefits of technology

It has achieved efficient filtration of PM0.3 and PM2.5, low air resistance, high adsorption efficiency of CO2, formaldehyde and CO, and demonstrates excellent carbon sequestration and low resistance filtration performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455682A_ABST
    Figure CN119455682A_ABST
Patent Text Reader

Abstract

The invention provides a polylactic acid fluffy nano fiber membrane capable of efficiently filtering out gas and particulate matters and a preparation method thereof. The method comprises the following steps: S1, preparing a stereocomplex crystal SC; step S2, preparing an SC crystal electret polylactic acid fluffy nano fiber membrane; step S3, preparing an MOF type nanocrystal growth precursor solution; and step S4, preparing the MOF SC crystal electret polylactic acid fluffy nano fiber membrane. The polylactic acid fluffy nano fiber membrane capable of efficiently filtering out the gas and the particulate matter can be used for scenes such as air purification, industrial waste gas treatment and indoor environment governance. The prepared MOF SC crystal electret polylactic acid fluffy nano fiber membrane has the advantages of high fluffy degree, high-efficiency low-resistance filtering performance, strong carbon sequestration performance and high formaldehyde and CO adsorption efficiency, and the application of a polylactic acid biological material in the fields of air purification and toxic gas trapping is effectively extended.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fully degradable fiber membrane materials for air purification and toxic gas adsorption, and in particular to a polylactic acid fluffy nanofiber membrane for efficiently filtering out gas and particulate matter and a preparation method thereof. Background Art

[0002] Air particulate matter pollution and toxic gases are major environmental and public health issues facing the world. Air particulate matter, especially PM 0.3 and PM 2.5 , can penetrate deep into the lungs and affect the heart and brain through blood circulation, leading to respiratory and cardiovascular diseases, and even increasing the risk of premature death. At the same time, toxic gases such as CO2, CO and volatile organic compounds pose a direct threat to human health and the ecological environment. CO2 can cause climate change, while CO can cause poisoning. Therefore, it is of great significance to develop multifunctional materials that can effectively solve the problems of air particulate pollution and toxic gas hazards.

[0003] Metal-organic framework (MOF) materials are porous materials formed by the combination of metal ions or metal clusters and organic ligands through coordination bonds. Due to their unique structure and excellent performance, they have shown wide application potential in the fields of gas adsorption, storage, catalysis and sensing. This type of material has a high porosity and adjustability, making its specific surface area up to 1000m 2 / g or higher, and can be flexibly designed to meet specific application requirements. Most MOF materials have good crystallinity and an ordered three-dimensional network structure, while different metal ions give them unique catalytic activity and selectivity. MOF performs well in the adsorption and separation of gases such as CO2, CH4, and H2, and exhibits good catalytic properties, making it suitable for organic synthesis and environmental catalysis. Therefore, MOF materials are becoming an important research object in fields such as materials science, environmental science, and biomedicine, and it is expected that more high-performance MOF materials will be developed in the future to meet the needs of different applications.

[0004] On the other hand, polylactic acid (PLA), as an ideal green material, is derived from starch extracted from plants and is widely used in the field of air filtration due to its excellent mechanical properties, biocompatibility and non-toxicity. Polylactic acid not only has excellent degradation performance, but also exhibits good biocompatibility. In addition, the molecular chain of polylactic acid contains chiral centers, which give it shear piezoelectricity and can generate voltage autonomously under mechanical action without the need for an external electric field for polarization treatment. This technical method is simple, efficient, and easy to achieve industrial production. By combining MOF materials with polylactic acid, not only can the performance of the filter material be significantly improved, but also the advantages of MOF can be effectively utilized to achieve efficient capture of particulate matter and effective adsorption of harmful gases. Summary of the invention

[0005] Purpose of the invention: To meet the needs of efficient air purification, the present invention proposes an innovative method, firstly, by preparing SC crystals and adding them as electrets to polylactic acid fibers to improve the interfacial polarization of the fiber membrane and promote the generation of deep charge traps. At the same time, a bulking agent is added to induce fiber fluffing. Then, through UV assistance and microwave catalysis, MOF-type nanocrystals are in situ synthesized on the surface of the fluffy fibers, and finally a MOF-type SC crystal electret polylactic acid fluffy nanofiber membrane with high fluffiness, high efficiency and low resistance filtration performance, excellent carbon fixation performance, and high efficiency adsorption of formaldehyde and CO is obtained. The application of this innovative material in the field of air purification and harmful gas capture has important practical significance and promotes the application scope of polylactic acid biomaterials.

[0006] The present invention provides a polylactic acid fluffy nanofiber membrane for efficiently filtering out gas and particulate matter and a preparation method thereof. The method comprises the following steps:

[0007] Step S1, preparing stereocomposite crystals SC: performing crystal treatment on left-handed polylactic acid PLLA and right-handed polylactic acid PDLA to obtain stereocomposite crystals SC;

[0008] Step S2, preparing SC crystal electret polylactic acid fluffy nanofiber film: firstly, dissolving polylactic acid in a solvent to prepare a polylactic acid solution, then using the stereocomposite crystal SC prepared in S1 as an electret material, adding the stereocomposite crystal SC to the polylactic acid solution, and adding a bulking agent to the polylactic acid solution to prepare a SC crystal electret polylactic acid fluffy nanofiber film with uniform-sized fibers through an electrospinning process;

[0009] Step S3, preparing a MOF type nanocrystal growth precursor solution: respectively dissolving a metal salt, a terephthalate reagent and an imidazole reagent in a solvent, then slowly adding the metal salt solution to a mixed solution of the terephthalate reagent and the imidazole reagent, and stirring and mixing them uniformly to obtain a MOF type nanocrystal growth precursor solution;

[0010] Step S4, preparing MOF-type SC crystal electret polylactic acid fluffy nanofiber membrane: immersing the SC crystal electret polylactic acid fluffy nanofiber membrane obtained in step S2 into the MOF type nanocrystal growth precursor solution obtained in step S3, and using microwave-assisted catalytic MOF type nanocrystals to grow at a constant temperature under ultraviolet UV irradiation conditions, and stirring to ensure the uniformity of the size of the MOF type nanocrystals grown on the fiber surface. After the growth is completed, rinse with the solution, and let it stand and dry to obtain the MOF-type SC crystal electret polylactic acid fluffy nanofiber membrane.

[0011] In step S1, the mass ratio of the left-handed polylactic acid PLLA to the right-handed polylactic acid PDLA is in the range of 1:9 to 9:1.

[0012] In step S1, the crystallization treatment method includes at least one of a solution method, a melt blending method, a freeze drying method, and a phase transition method;

[0013] The solution method comprises: dissolving the left-handed polylactic acid PLLA and the right-handed polylactic acid PDLA respectively using at least one of dimethylformamide, dichloromethane, chloroform, acetone, hexafluoroisopropanol and ethyl acetate as solvents, setting the stirring speed to 100-500 rpm, dissolving the left-handed polylactic acid PLLA and the right-handed polylactic acid PDLA to obtain the left-handed polylactic acid PLLA solution and the right-handed polylactic acid PDLA solution respectively, wherein the mass ratio of the left-handed polylactic acid PLLA to the solvent is 5%-30%, and the mass ratio of the right-handed polylactic acid PDLA to the solvent is 5%-30%; then stirring and mixing the left-handed polylactic acid PLLA solution and the right-handed polylactic acid PDLA solution at a stirring speed of 100-500 rpm to obtain a mixed solution, and solidifying and crystallizing the mixed solution by solvent evaporation or gelation to obtain stereocomposite crystals SC; wherein the solvent evaporation temperature is 20°C-250°C, and the gelation temperature is 20°C-60°C;

[0014] The melt blending method comprises: melting left-handed polylactic acid PLLA and right-handed polylactic acid PDLA at a high temperature of 170°C to 300°C, stirring at a speed of 100 to 500 rpm during melting, and cooling at -10°C to 30°C to obtain stereocomposite crystals SC;

[0015] The freeze-drying method comprises: using at least one of dimethylformamide, dichloromethane, chloroform, acetone, hexafluoroisopropanol, and ethyl acetate as a solvent, adding L-polylactic acid PLLA and D-polylactic acid PDLA into the solvent respectively, setting a stirring speed of 100 to 500 rpm, and obtaining L-polylactic acid PLLA solution and D-polylactic acid PDLA solution respectively, wherein the mass ratio of L-polylactic acid PLLA to the solvent is 5% to 30%, and the mass ratio of D-polylactic acid PDLA to the solvent is 5% to 30%, mixing the L-polylactic acid PLLA solution and the D-polylactic acid PDLA solution, stirring at a speed of 100 to 500 rpm during mixing, and then freeze-molding at an ultra-low temperature of -150°C to -50°C, and drying at -20°C to -49°C to remove the solvent, to form a stereocomposite crystal SC;

[0016] The phase transition method comprises: using at least one of dimethylformamide, dichloromethane, chloroform, acetone, hexafluoroisopropanol and ethyl acetate as a solvent, adding L-polylactic acid PLLA and D-polylactic acid PDLA into the solvent respectively, setting the stirring speed to 100-500 rpm, obtaining L-polylactic acid PLLA solution and D-polylactic acid PDLA solution respectively, wherein the mass ratio of L-polylactic acid PLLA to the solvent is 5%-30%, and the mass ratio of D-polylactic acid PDLA to the solvent is 5%-30%, mixing the L-polylactic acid PLLA solution and the D-polylactic acid PDLA solution, stirring the solution at a speed of 100-500 rpm during mixing, then setting the cooling temperature to -20°C to -100°C, and the temperature change rate to 1°C / min to 5°C / min, to form stereocomposite crystals SC.

[0017] In step S2, the proportion of polylactic acid in the polylactic acid solution is 5% to 25%, the mass ratio of the stereocomplex crystal SC to the polylactic acid is 1:20 to 1:2, the solvent used is at least one of dimethylformamide, dichloromethane, chloroform, acetone, hexafluoroisopropanol, and ethyl acetate, the bulking agent is at least one of cellulose acetate, polyvinyl alcohol, polyurethane, polycaprolactone, chitosan and polylactic acid copolymer, and the mass ratio of the bulking agent to the polylactic acid is 1:10 to 2:1.

[0018] In step S2, when the electrospinning process is adopted, the output voltage of the electrospinning is 5 to 35 kV, the solution consumption rate is 0.5 to 4 mL / h, the spinning and winding speed is 100 to 1500 rpm, the receiving distance is 8 to 30 cm, the spinning temperature is 20 to 50 ° C, the humidity is 50% to 90%, the average diameter of the polylactic acid fluffy nanofibers is 200 to 990 nm, and the thickness of the polylactic acid fluffy nanofiber film is 300 to 1000 μm;

[0019] In step S3, the metal salt is at least one of zinc nitrate (magnesium nitrate, iron nitrate, copper nitrate), zinc acetate (magnesium acetate, iron acetate, copper acetate), zinc sulfate (magnesium sulfate, iron sulfate, copper sulfate), zinc chloride (magnesium chloride, iron chloride, copper chloride), and zinc oxide (magnesium oxide, iron oxide, copper oxide).

[0020] In step S3, the terephthalate reagent is at least one of terephthalic acid, sodium terephthalate, ammonium terephthalate, dimethyl terephthalate, and ammonium hydrogen terephthalate;

[0021] The imidazole reagent is at least one of methylimidazole, dimethylimidazole, 2-aminobenzimidazole, 2-aminoimidazole, 1-3-aminopropylimidazole, 4-aminoimidazole, and imidazolylbenzene;

[0022] The solvent is at least one of dimethylsulfamide, dimethylformamide, deionized water, ethanol, methanol, n-butanol, isopropanol, ethylene glycol, and chloroform;

[0023] The mass ratio of the metal salt to the terephthalate reagent is 1:8-1:1;

[0024] The mass ratio of the metal salt to the imidazole reagent is 1:10 to 1:1;

[0025] The mass ratio of the metal salt to the solvent is 1:1000 to 1:50;

[0026] When stirring, the stirring speed is 100 to 600 rpm and the stirring time is 20 to 40 minutes.

[0027] In step S4, the microwave output power used is 300-1200W, the growth temperature is 150-250°C, the synthesis time is 20-100min, the stirring speed is 10-300rpm, the wavelength range of ultraviolet light UV is 100-400nm, and the irradiation intensity is 100-500mW / cm 2 The irradiation time is the same as the synthesis time, the ultraviolet UV light source is at least one of a mercury lamp, a xenon lamp, an LED UV light source, a black light lamp, an ultraviolet lamp tube, and a nitrogen laser, and the average particle size of the MOF nanocrystals is 100 to 990 nm.

[0028] In step S4, the drying method used is at least one of natural drying, hot air drying, freeze drying, vacuum drying, microwave drying, spray drying, flash drying, and radiation drying.

[0029] The invention also provides a polylactic acid fluffy nanofiber membrane for efficiently filtering out gas and particulate matter, which is prepared by the method described.

[0030] The polylactic acid fluffy nanofiber membrane for efficiently filtering out gas and particulate matter provided by the present invention can be used in scenarios such as air purification, industrial waste gas treatment and indoor environmental management. In air purification equipment, the membrane can be integrated into the filter to efficiently remove tiny particles and common harmful gases in the air, such as PM 2.5 , CO2, formaldehyde and CO, improving air quality. In the field of personal protection, the material can be used to make masks, providing high air permeability and low resistance, while effectively filtering viruses, bacteria and other air pollutants to meet the needs of efficient protection. For industrial waste gas treatment, the material has excellent performance in capturing dust and adsorbing toxic gases, and can achieve pollutant removal at low energy consumption, providing a new option for environmental protection equipment. In addition, the material is also suitable for indoor air purification products such as air purifiers and ventilation filtration systems to help improve indoor environmental quality and protect people's respiratory health.

[0031] Beneficial effects: The polylactic acid fluffy nanofiber membrane with high efficiency in filtering out gas and particulate matter and its preparation method are prepared by preparing SC crystal electret polylactic acid fluffy nanofiber membrane, and synthesizing MOF type nanocrystals on the surface of each fiber in the fiber membrane by the "microwave catalysis + UV assisted" in-situ growth method, relying on the fluffy characteristics of the fiber, to obtain SC crystal electret polylactic acid fluffy nanofiber membrane fully loaded with MOF type nanocrystals. The fiber diameter of the nanofiber membrane is 200-990nm, the thickness of the fiber membrane is 300-1000μm, and the PM is 1.376 W / m at 85L / min. 0.3 The filtration efficiency is 96.5% to 97.8% for PM 2.5 The filtration efficiency is 99.2% to 99.7%, the air resistance is 100 to 140 Pa, the adsorption efficiency of CO2 is 80% to 85%, the adsorption efficiency of formaldehyde is 82% to 88%, and the adsorption efficiency of CO can reach more than 80%. The preparation method is simple and the conditions are controllable. The prepared MOF-SC crystal electret polylactic acid fluffy nanofiber membrane has the advantages of high fluffiness, high efficiency and low resistance filtration performance, strong carbon fixation performance, and high efficiency formaldehyde and CO adsorption performance, which effectively extends the application of polylactic acid biomaterials in the fields of air purification and toxic gas capture. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0033] Figure 1 It is a flow chart of the method of the present invention.

[0034] Figure 2 This is a schematic diagram of the morphology of the SC crystal prepared in Example 1 observed by SEM.

[0035] Figure 3 This is a schematic diagram of the morphology of the SC crystal electret polylactic acid fluffy fiber film prepared in Example 2 observed by SEM.

[0036] Figure 4 This is a schematic diagram of the morphology of the MOF-type nanocrystals prepared in Example 3 observed by SEM.

[0037] Figure 5 This is a schematic diagram of the morphology of the MOF-based SC crystal electret polylactic acid fluffy nanofiber membrane prepared in Example 4 observed by SEM. DETAILED DESCRIPTION

[0038] Example 1

[0039] This embodiment provides a method for preparing a polylactic acid fluffy nanofiber membrane for efficiently filtering out gas and particulate matter, comprising the following steps:

[0040] S11. Preparation of stereocomposite crystal (SC): PLLA and PDLA were crystallized by a solution method. Specifically, 1 g of PLLA and 1 g of PDLA were dissolved in 10 g of dichloromethane respectively. After the two solutions were completely dissolved, they were mixed at a speed of 300 rpm, and then solidified and crystallized at a temperature of 180° C. to obtain SC crystal.

[0041] S12, preparation of SC crystal electret polylactic acid fluffy nanofiber membrane: the SC crystal prepared by S11 was used as the electret material, first 0.1g SC crystal was dispersed in 3g of dichloromethane, then 0.5g polylactic acid and 0.5g cellulose acetate were dissolved in 7g of dichloromethane, and then they were evenly mixed to prepare a spinning solution, and then 2mL of the spinning solution was taken for electrostatic spinning, wherein the set output voltage was 24kV, the solution advancing speed was 1.5mL / h, the fiber winding speed was 500rpm, the spinning temperature was 40°C, and the humidity was 70%, and the SC crystal electret polylactic acid fluffy nanofiber membrane was spun, wherein the average fiber diameter of the fiber membrane was 800nm ​​and the membrane thickness was 900μm;

[0042] S13, preparation of MOF type nanocrystal growth precursor solution: first, take 0.5g zinc nitrate and dissolve it in 100mL water, then take 1.5g terephthalic acid and 2.5g methylimidazole and dissolve them in 100mL water respectively, mix the above solutions under 300rpm magnetic stirring until they are completely dissolved, and stir for 30min to make the solutions completely mixed, to obtain MOF type nanocrystal growth precursor solution;

[0043] S14, preparation of MOF-based SC crystal electret polylactic acid fluffy nanofiber membrane: The SC crystal electret polylactic acid fluffy nanofiber membrane obtained in S12 was immersed in the MOF-type nanocrystal growth precursor solution obtained in S13, and a mercury lamp was used to provide light with a wavelength of 300 nm, and the irradiation intensity was set to 250 mW / cm 2 , and then microwave-assisted catalytic growth was performed, wherein the microwave output power was 800 W, the growth temperature was 200 ° C, the synthesis time was set to 50 min, the stirring speed was 100 rpm, and deionized water was used for rinsing after the reaction was completed. After standing and drying, a MOF-type SC crystal electret polylactic acid fluffy nanofiber membrane was obtained, wherein the average size of the MOF nanocrystals synthesized on the surface of the nanofiber was 300 nm.

[0044] Example 2

[0045] This embodiment provides a method for preparing a polylactic acid fluffy nanofiber membrane for efficiently filtering out gas and particulate matter, comprising the following steps:

[0046] S21. Preparation of stereocomposite crystal (SC): PLLA and PDLA were crystallized by melt blending. Specifically, 1.2 g of PLLA and 0.8 g of PDLA were melted at 250° C., mixed uniformly at 400 rpm, and then transferred to 0° C. environment for quenching and crystallization to obtain SC crystal.

[0047] S22, preparation of SC crystal electret polylactic acid fluffy nanofiber membrane: the SC crystal prepared by S21 was used as the electret material, first 0.12g of SC crystal was dispersed in 3g of acetone, then 1.2g of polylactic acid and 0.8g of polyvinyl alcohol were dissolved in 7g of acetone, and then they were evenly mixed to prepare a spinning solution, and then 1mL of the spinning solution was taken for electrostatic spinning, wherein the set output voltage was 35kV, the solution advancing speed was 0.5mL / h, the fiber winding speed was 1000rpm, the spinning temperature was 20°C, and the humidity was 50%, and SC crystal electret polylactic acid fluffy nanofiber membrane was spun, wherein the average fiber diameter of the fiber membrane was 700nm and the membrane thickness was 800μm;

[0048] S23, preparation of MOF type nanocrystal growth precursor solution: first, take 0.8g of magnesium acetate and dissolve it in 100mL of ethanol, then take 1.6g of sodium terephthalate and 8g of methylimidazole and dissolve them in 100mL of ethanol respectively, mix the above solutions under magnetic stirring at 600rpm until they are completely dissolved, and stir for 20min to make the solutions completely mixed, to obtain MOF type nanocrystal growth precursor solution;

[0049] S24, preparation of MOF-based SC crystal electret polylactic acid fluffy nanofiber membrane: The SC crystal electret polylactic acid fluffy nanofiber membrane obtained in S22 was immersed in the MOF-type nanocrystal growth precursor solution obtained in S23, and a xenon lamp was used to provide light with a wavelength of 400 nm, and the irradiation intensity was set to 100 mW / cm 2 , and then microwave-assisted catalytic growth was performed, wherein the microwave output power was 400 W, the growth temperature was 150 ° C, the synthesis time was set to 100 min, the stirring speed was 10 rpm, and deionized water was used for rinsing after the reaction was completed. After standing and drying, a MOF-type SC crystal electret polylactic acid fluffy nanofiber membrane was obtained, wherein the average size of the MOF nanocrystals synthesized on the surface of the nanofiber was 400 nm.

[0050] Example 3

[0051] This embodiment provides a method for preparing a polylactic acid fluffy nanofiber membrane for efficiently filtering out gas and particulate matter, comprising the following steps:

[0052] S31. Preparation of stereocomposite crystal (SC): PLLA and PDLA were crystallized by freeze drying. Specifically, 0.8 g of PLLA and 1.2 g of PDLA were dissolved in 10 g of chloroform respectively. After they were completely dissolved, the two solutions were mixed at a speed of 300 rpm. Then, the two solutions were solidified at a temperature of -100°C. Then, the solvent was removed by drying at -40°C to obtain SC crystal.

[0053] S32, SC crystal electret polylactic acid fluffy nanofiber film preparation: the SC crystal prepared by S31 is used as the electret material, first 0.08g SC crystal is dispersed in 2g chloroform, then 1.6g polylactic acid and 0.4g polyurethane are dissolved in 8g chloroform, and then they are evenly mixed to prepare a spinning solution, and then 1mL of the spinning solution is taken for electrostatic spinning, wherein the set output voltage is 30kV, the solution advancing speed is 0.8mL / h, the fiber winding speed is 1500rpm, the spinning temperature is 30℃, and the humidity is 60%, and the SC crystal electret polylactic acid fluffy nanofiber film is spun, wherein the average fiber diameter of the fiber membrane is 750nm and the membrane thickness is 850μm;

[0054] S33, preparation of MOF type nanocrystal growth precursor solution: first, take 0.5g of ferric sulfate and dissolve it in 100mL of methanol, then take 4g of ammonium terephthalate and 0.7g of 2-aminobenzimidazole and dissolve them in 200mL of methanol respectively, mix the above solutions under 500rpm magnetic stirring until they are completely dissolved, and stir for 40min to make the solutions completely mixed, to obtain MOF type nanocrystal growth precursor solution;

[0055] S34, preparation of MOF-based SC crystal electret polylactic acid fluffy nanofiber film: the SC crystal electret polylactic acid fluffy nanofiber film obtained in S32 is immersed in the MOF-type nanocrystal growth precursor solution obtained in S33, and a LED UV light source is used to provide light with a wavelength of 100 nm, and the irradiation intensity is set to 500 mW / cm 2 , and then microwave-assisted catalytic growth was performed, wherein the microwave output power was 700 W, the growth temperature was 250 ° C, the synthesis time was set to 20 min, the stirring speed was 100 rpm, and deionized water was used for rinsing after the reaction. After standing and drying, a MOF-type SC crystal electret polylactic acid fluffy nanofiber membrane was obtained, wherein the average size of the MOF nanocrystals synthesized on the surface of the nanofiber was 200 nm.

[0056] Example 4

[0057] This embodiment provides a method for preparing a polylactic acid fluffy nanofiber membrane for efficiently filtering out gas and particulate matter, comprising the following steps:

[0058] S41. Preparation of stereocomposite crystal (SC): PLLA and PDLA were crystallized by phase transformation method. Specifically, 1 g of PLLA and 1 g of PDLA were dissolved in 10 g of dimethylformamide and 10 g of chloroform respectively. After they were completely dissolved, the two solutions were mixed at a speed of 500 rpm. Then, the cooling temperature was set to -80°C, the temperature change rate was set to 4°C / min, and the solution stirring speed was set to 400 rpm. After the solution was completely solidified and crystallized, SC crystals were obtained.

[0059] S42, SC crystal electret polylactic acid fluffy nanofiber film preparation: The SC crystal prepared by S41 is used as the electret material, first 0.3g of SC crystal is dispersed in 4g of chloroform, then 0.3g of polylactic acid and 0.4g of polyurethane are dissolved in 6g of dimethylformamide, and then they are uniformly mixed to prepare a spinning solution, and then 1.4mL of the spinning solution is taken for electrostatic spinning, wherein the set output voltage is 20kV, the solution advancing speed is 3mL / h, the fiber winding speed is 300rpm, the spinning temperature is 50°C, and the humidity is 50%, and the SC crystal electret polylactic acid fluffy nanofiber film is spun, wherein the average fiber diameter of the fiber membrane is 1000nm and the membrane thickness is 600μm;

[0060] S43, preparation of MOF type nanocrystal growth precursor solution: first, take 1g of copper oxide and dissolve it in 100mL of methanol, then take 2g of dimethyl terephthalate and 1g of 4-aminoimidazole and dissolve them in 100mL of water respectively, mix the above solutions under 500rpm magnetic stirring until they are completely dissolved, and stir for 30min to make the solutions completely mixed, to obtain MOF type nanocrystal growth precursor solution;

[0061] S44, preparation of MOF-based SC crystal electret polylactic acid fluffy nanofiber film: immerse the SC crystal electret polylactic acid fluffy nanofiber film obtained in S42 into the MOF type nanocrystal growth precursor solution obtained in S43, and provide light with a wavelength of 200nm through an ultraviolet lamp, and set the irradiation intensity to 450mW / cm 2 , and then microwave-assisted catalytic growth was performed, wherein the microwave output power was 900 W, the growth temperature was 180 ° C, the synthesis time was set to 40 min, the stirring speed was 300 rpm, and deionized water was used for rinsing after the reaction. After standing and drying, a MOF-type SC crystal electret polylactic acid fluffy nanofiber membrane was obtained, wherein the average size of the MOF nanocrystals synthesized on the surface of the nanofiber was 250 nm.

[0062] Comparative Example 1 (No Fluffy Fiber Preparation)

[0063] The MOF-SC-crystal electret polylactic acid fluffy nanofiber membrane was prepared basically by the method of Example 1. The difference was that no bulking agent was added during electrospinning in this example. Specifically, S11, preparation of stereocomposite crystal (SC): PLLA and PDLA are crystallized by a solution method, specifically: 1g of PLLA and 1g of PDLA are respectively dissolved in 10g of dichloromethane, and after complete dissolution, the two solutions are mixed evenly at a speed of 300rpm, and then solidified and crystallized at a temperature of 180°C to obtain SC crystals; S12, preparation of SC crystal electret polylactic acid nanofiber film: The SC crystal prepared by S11 is used as an electret material, first 0.1g of SC crystal is dispersed in 3g of dichloromethane, and then 1g of polylactic acid is dissolved in 7g of dichloromethane, and then they are evenly mixed to prepare a spinning solution, and then 2mL of the spinning solution is taken for electrostatic spinning, wherein the set output voltage is 24kV, the solution propulsion speed is 1.5mL / h, and the fiber winding speed is 50 0rpm, spinning temperature of 40℃, humidity of 70%, spinning into SC crystal electret polylactic acid nanofiber membrane; S13, preparation of MOF type nanocrystal growth precursor solution: first take 0.5g zinc nitrate and dissolve it in 100mL water, then take 1.5g terephthalic acid and 2.5g methylimidazole and dissolve them in 100mL water respectively, mix the above solutions under 300rpm magnetic stirring with complete dissolution, and stir for 30min to make the solution completely mixed, to obtain MOF type nanocrystal growth precursor solution; S14, MOF SC crystal electret polylactic acid fluffy nanofiber membrane preparation: soak the SC crystal electret polylactic acid nanofiber membrane obtained in S12 into the MOF type nanocrystal growth precursor solution obtained in S13, provide light of 300nm wavelength through a mercury lamp, and set the irradiation intensity to 250mW / cm 2 , and then microwave-assisted catalytic growth was performed, wherein the microwave output power was 800 W, the growth temperature was 200 ° C, the synthesis time was set to 50 min, the stirring speed was 100 rpm, and after the reaction was completed, deionized water was used for rinsing, and the MOF-based SC crystal electret polylactic acid fluffy nanofiber membrane was obtained after standing and drying.

[0064] Comparative Example 2 (UV-assisted + microwave catalysis is not used to promote in-situ synthesis in the preparation of MOF-SC crystal electret polylactic acid fluffy nanofiber film)

[0065] The method of Example 2 is basically adopted to prepare MOF-based SC crystal electret polylactic acid fluffy nanofiber membrane. The difference is that in this example, UV assistance + microwave catalysis is not used to promote in-situ synthesis in the preparation of MOF-based SC crystal electret polylactic acid fluffy nanofiber membrane. Specifically, S21, preparation of stereocomposite crystal (SC): PLLA and PDLA are crystallized by melt blending. Specifically: 1.2g of PLLA and 0.8g of PDLA are melted at a high temperature of 250°C respectively, and mixed evenly at a speed of 400rpm, and then transferred to a 0°C environment for rapid cooling and crystallization to obtain SC crystals; S22, preparation of SC crystal electret polylactic acid fluffy nanofiber membrane: The SC crystals prepared in S21 are used as electret materials. First, take 0.12g SC crystals were dispersed in 3g acetone, and then 1.2g polylactic acid and 0.8g polyvinyl alcohol were dissolved in 7g acetone, and then they were uniformly mixed to prepare a spinning solution, and then 1mL of the spinning solution was taken for electrospinning, wherein the output voltage was set to 35kV, the solution advancing speed was 0.5mL / h, the fiber winding speed was 1000rpm, the spinning temperature was 20℃, and the humidity was 50%, and the SC crystal electret polylactic acid fluffy nanofiber membrane was spun, wherein the fiber of the fiber membrane The average diameter is 700nm and the film thickness is 800μm; S23, preparation of MOF type nanocrystal growth precursor solution: first, take 0.8g magnesium acetate and dissolve it in 100mL ethanol, then take 1.6g sodium terephthalate and 8g methylimidazole and dissolve them in 100mL ethanol respectively, mix the above solutions under 600rpm magnetic stirring until they are completely dissolved, and stir for 20min to make the solutions completely mixed to obtain MOF type nanocrystal growth precursor solution; S24, MOF Preparation of SC crystal electret polylactic acid fluffy nanofiber membrane: The SC crystal electret polylactic acid fluffy nanofiber membrane obtained in S22 is immersed in the MOF type nanocrystal growth precursor solution obtained in S23, the growth temperature is set to 150°C, the synthesis time is set to 100min, the stirring speed is 10rpm, and after the reaction is completed, it is rinsed with deionized water. After standing and drying, a MOF SC crystal electret polylactic acid fluffy nanofiber membrane is obtained, wherein the average size of the MOF nanocrystals synthesized on the surface of the nanofiber is 400nm.

[0066] Comparative Example 3 (No Growth of MOF Nanocrystals)

[0067] The method of Example 3 is basically adopted to prepare the polylactic acid fluffy nanofiber membrane, except that in this example, MOF nanocrystals are not grown on the surface of the polylactic acid fluffy nanofiber membrane. Specifically, S31, preparation of stereocomposite crystal (SC): PLLA and PDLA are crystallized by freeze drying, specifically: 0.8g of PLLA and 1.2g of PDLA are dissolved in 10g of chloroform respectively, and after they are completely dissolved, the two solutions are mixed evenly at a speed of 300rpm, and then cured at a temperature of -100°C, and then dried at -40°C to remove the solvent to obtain SC crystals; S32, preparation of SC crystal electret polylactic acid fluffy nanofiber membrane: The SC crystals prepared in S31 are used as electret materials, first 0.08g of SC crystals are dispersed in 2g of chloroform, and then Then, 1.6 g of polylactic acid and 0.4 g of polyurethane were dissolved in 8 g of chloroform, and then uniformly mixed to prepare a spinning solution, and then 1 mL of the spinning solution was taken for electrostatic spinning, wherein the set output voltage was 30 kV, the solution propulsion speed was 0.8 mL / h, the fiber winding speed was 1500 rpm, the spinning temperature was 30 ° C, and the humidity was 60%, and SC crystal electret polylactic acid fluffy nanofiber membrane was spun, wherein the average fiber diameter of the fiber membrane was 750 nm and the membrane thickness was 850 μm. In order to ensure the consistency of the remaining steps, the prepared SC crystal electret polylactic acid fluffy nanofiber membrane was placed in a methanol solution, and then a LED UV light source was used to provide light with a wavelength of 100 nm, and the irradiation intensity was set to 500 mW / cm 2 , and then microwave-assisted catalytic growth was performed, wherein the microwave output power was 700 W, the growth temperature was 250°C, the synthesis time was set to 20 min, the stirring speed was 100 rpm, and after the reaction was completed, deionized water was used for rinsing, and the nanofiber membrane was obtained after standing and drying.

[0068] Structural characterization and performance testing:

[0069] Scanning electron microscope (SEM) observation: The microstructures of SC crystals, SC crystal electret polylactic acid fluffy nanofiber membranes, MOF-type nanocrystals, and MOF-type SC crystal electret polylactic acid fluffy nanofiber membranes were observed by field emission scanning electron microscope (model JSM-7900F, Japan Electronics). Figure 2 , Figure 3 , Figure 4 and Figure 5 shown).

[0070] Nanofiber membrane thickness and fiber diameter test: The thickness of the nanofiber membrane was tested using a spiral micrometer; the fiber diameter was calculated using ImageJ software to obtain the average fiber diameter.

[0071] Filtration performance test: The filtration performance of a circular nanofiber membrane with a diameter of 10 cm was tested using a self-built filtration performance test system. The air flow rate was set to 85 L / min, and the particle size range of the NaCl atomized particles produced by the aerosol generator was 0.3-2.5 μm. The particle concentration upstream and downstream of the nanofiber membrane was measured by using a P-Trak particle counter (model 3910, TSI, USA; model 3330, TSI, USA), and the air resistance was measured using a micromanometer (AP800, TSI, USA). Finally, the filtration efficiency and pressure drop were calculated.

[0072] CO2 adsorption performance test: Relying on the self-built gas adsorption performance test platform, medical-grade CO2 with a concentration of 99.5% was used, and a standard commercial regulator was used to introduce an appropriate amount of CO2 into the test bench. A portable CO2 sensor was used to monitor the concentration of CO2 in real time, and the initial concentration and the concentration after 1 hour of adsorption were recorded to calculate the adsorption efficiency of CO2 by the nanofiber membrane.

[0073] CO adsorption performance test: Relying on other adsorption performance test platforms built independently, an appropriate amount of CO was introduced into the test bench through a standard commercial regulator. The concentration of CO was monitored in real time using a portable CO sensor, and the initial concentration and the concentration after 1 hour of adsorption were recorded to calculate the adsorption efficiency of CO by the nanofiber membrane.

[0074] Formaldehyde adsorption performance test: Relying on the self-built gas adsorption performance test platform, a standard commercial regulator is used to introduce an appropriate amount of formaldehyde into the test bench. The formaldehyde concentration is monitored in real time using a formaldehyde sensor, and the initial concentration and the concentration after 1 hour of adsorption are recorded to calculate the formaldehyde adsorption efficiency of the nanofiber membrane.

[0075] Experimental results: The technical solution described in this embodiment is as follows Figure 1 As shown, the main experimental materials and preparation and modification methods in this embodiment are described in detail, which is helpful for the preparation of MOF-based SC crystal electret polylactic acid fluffy nanofiber membrane. Figure 2 The surface morphology of the SC crystals prepared in Example 1 is shown. It can be clearly found that the SC crystals prepared by the solution method have uniform morphology and uniform size, which is conducive to adding them to polylactic acid as an electret material to improve the polarization properties of polylactic acid. Figure 3As shown, the surface morphology of the SC crystal electret polylactic acid fluffy fiber membrane prepared in Example 2 is shown. It can be found that the fiber presents an irregular structure and there are grooves in the fiber code, which is beneficial to increase the specific surface area of ​​the fiber membrane and increase the contact sites for the growth of MOF nanocrystals on the fiber surface. It can be found that there are protrusions in the fiber, which is mainly due to the addition of SC crystals. The addition of SC crystals can significantly improve the interfacial polarization properties of the fiber. At the same time, deep charge traps will be generated at the interface, which is of great significance for better storage of charges and improving the electrostatic adsorption capacity of the fiber membrane to particulate matter.

[0076] Figure 4 The surface morphology of the MOF nanocrystals prepared in Example 3 is shown. It can be found that the size of the MOF nanocrystals prepared by UV assistance and microwave catalysis is relatively uniform, with an average size of about 200nm. The combined action of UV and microwave not only significantly shortens the synthesis time and improves the preparation efficiency of MOF, but also helps to adjust the porosity and pore size distribution of MOF, optimize its gas adsorption performance, and promote the self-assembly process of organic ligands and metal ions, increasing the stability and structural integrity of MOF. In addition, Figure 5 The morphology of the MOF-SC crystal electret polylactic acid fluffy nanofiber membrane prepared in Example 4 is shown. It can be found that MOF-type nanocrystals are uniformly grown on the surface of the fiber, which is of great significance for improving the filtration performance of the fiber membrane for particulate matter and the adsorption performance for gas.

[0077] Table 1 shows the performance test results of Examples 1 to 4 and Comparative Examples 1 to 3. It can be seen from the table that the thickness of the nanofiber membranes of Examples 1 to 4 can reach up to 900 μm, and the nanofiber membranes have excellent fluffiness, which is conducive to the growth of MOF nanocrystals on the fibers; and by regulating the electrospinning process, the fiber diameter of the fiber membrane is controlled at the nanometer level, which is more conducive to the effective interception of ultrafine particles. At the same time, by filtering PM at a high air flow rate of 85 L / min 2.5 and PM 0.3 The performance of PM was measured, as shown in Table 1. 0.3 The filtration efficiency can reach 96.5% to 97.8% for PM 2.5The filtration efficiency can reach 99.2% to 99.7%. Compared with comparative examples 1 to 3, the embodiment shows more excellent filtration performance. At the same time, the fluffy fiber structure is more conducive to air circulation, thereby significantly reducing the air resistance of the nanofiber membrane (below 140Pa). Compared with Comparative Example 1, the excellent filtration performance is manifested in the dense fiber structure, which contributes to high filtration efficiency but also causes high air resistance; compared with Comparative Example 2, since UV assistance + microwave catalysis is not used to promote the in-situ synthesis of MOF nanocrystals, it is difficult to achieve complete synthesis of nanocrystals in a short time, so it is impossible to form a nanofiber membrane with a larger specific surface area to improve the filtration efficiency, resulting in a decrease in the particle removal performance; compared with Comparative Example 3, the obtained SC crystal electret polylactic acid fluffy nanofiber membrane is soaked in methanol, and after UV and microwave treatment, since MOF nanocrystals are in-situ synthesized on the fiber surface, and the presence of methanol eliminates the initial charge on the fiber membrane surface, although the deep charge traps generated by interfacial polarization can retain part of the charge, the loss of a large amount of surface charge and the large fiber gaps inside the fiber membrane can easily cause the passage of fine particles, thereby causing PM 0.3 and PM 2.5 The filtration performance of the filter decreases, but because MOF nanocrystals are not grown, the large pores ensure low air resistance.

[0078] Table 1

[0079]

[0080] Table 2 compares the adsorption performance of MOF-SC electret polylactic acid fluffy nanofiber membranes for CO2, formaldehyde and CO. It can be found that the adsorption efficiency of CO2 in Examples 1 to 4 is 83.6% to 85.1%, and the adsorption efficiency of formaldehyde is 82.1% to 97.2%. The adsorption efficiency of CO is 80.3% to 96.2%, which is mainly due to the uniform growth of MOF nanocrystals on the fiber surface, which provides a higher specific surface area for the fiber membrane, and the fluffy fibers can provide more sites for contact with the gas, thereby providing higher adsorption for the gas, and UV irradiation can optimize the pore structure of MOF nanocrystals, thereby increasing its specific surface area and pore volume, and improving the adsorption capacity for gas, so that it has greater potential in applications such as gas separation, storage and capture.

[0081] Table 2

[0082]

[0083]

[0084] This shows that, by adopting the method of the present invention, SC crystals are prepared and added as electrets to polylactic acid fibers to improve the interfacial polarization of the fiber membrane, promote the generation of deep charge traps, and simultaneously add a bulking agent to induce the fiber to fluff up. Then, MOF-type nanocrystals are in situ synthesized on the surface of the fluffy fibers through UV assistance + microwave catalysis, thereby obtaining a MOF-type SC crystal electret polylactic acid fluffy nanofiber membrane with high fluffiness, high-efficiency and low-resistance filtration performance, strong carbon fixation performance, and high-efficiency formaldehyde and CO adsorption performance. This is of great significance for extending the application of polylactic acid biomaterials in the fields of air purification and toxic gas capture.

[0085] The present invention provides a polylactic acid fluffy nanofiber membrane for efficiently filtering gas and particulate matter and a preparation method thereof. There are many methods and approaches to specifically implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be considered as the protection scope of the present invention. All components not specified in this embodiment can be implemented using existing technologies.

Claims

1. A method for preparing a polylactic acid fluffy nanofiber membrane for efficiently filtering out gas and particulate matter, characterized in that: The following steps are involved: Step S1, preparing stereocomposite crystals SC: performing crystal treatment on left-handed polylactic acid PLLA and right-handed polylactic acid PDLA to obtain stereocomposite crystals SC; Step S2, preparing SC crystal electret polylactic acid fluffy nanofiber film: firstly, dissolving polylactic acid in a solvent to prepare a polylactic acid solution, then using the stereocomposite crystal SC prepared in S1 as an electret material, adding the stereocomposite crystal SC to the polylactic acid solution, and adding a bulking agent to the polylactic acid solution to prepare a SC crystal electret polylactic acid fluffy nanofiber film with uniform-sized fibers through an electrospinning process; Step S3, preparing a MOF type nanocrystal growth precursor solution: respectively dissolving a metal salt, a terephthalate reagent and an imidazole reagent in a solvent, then slowly adding the metal salt solution to a mixed solution of the terephthalate reagent and the imidazole reagent, and stirring and mixing them uniformly to obtain a MOF type nanocrystal growth precursor solution; Step S4, preparing MOF-type SC crystal electret polylactic acid fluffy nanofiber membrane: immersing the SC crystal electret polylactic acid fluffy nanofiber membrane obtained in step S2 into the MOF type nanocrystal growth precursor solution obtained in step S3, and using microwave-assisted catalytic MOF type nanocrystals to grow at a constant temperature under ultraviolet UV irradiation conditions, and stirring to ensure the uniformity of the size of the MOF type nanocrystals grown on the fiber surface. After the growth is completed, rinse with the solution, and let it stand and dry to obtain the MOF-type SC crystal electret polylactic acid fluffy nanofiber membrane.

2. The method according to claim 1, characterized in that In step S1, the mass ratio of the left-handed polylactic acid PLLA to the right-handed polylactic acid PDLA is in the range of 1:9 to 9:

1.

3. The method according to claim 2, characterized in that In step S1, the crystallization treatment method includes at least one of a solution method, a melt blending method, a freeze drying method, and a phase transition method; The solution method comprises: dissolving the left-handed polylactic acid PLLA and the right-handed polylactic acid PDLA respectively using at least one of dimethylformamide, dichloromethane, chloroform, acetone, hexafluoroisopropanol and ethyl acetate as solvents, setting the stirring speed to 100-500 rpm, dissolving the left-handed polylactic acid PLLA and the right-handed polylactic acid PDLA to obtain the left-handed polylactic acid PLLA solution and the right-handed polylactic acid PDLA solution respectively, wherein the mass ratio of the left-handed polylactic acid PLLA to the solvent is 5%-30%, and the mass ratio of the right-handed polylactic acid PDLA to the solvent is 5%-30%; then stirring and mixing the left-handed polylactic acid PLLA solution and the right-handed polylactic acid PDLA solution at a stirring speed of 100-500 rpm to obtain a mixed solution, and solidifying and crystallizing the mixed solution by solvent evaporation or gelation to obtain stereocomposite crystals SC; wherein the solvent evaporation temperature is 20°C-250°C, and the gelation temperature is 20°C-60°C; The melt blending method comprises: melting left-handed polylactic acid PLLA and right-handed polylactic acid PDLA at a high temperature of 170°C to 300°C, stirring at a speed of 100 to 500 rpm during melting, and cooling at -10°C to 30°C to obtain stereocomposite crystals SC; The freeze-drying method comprises: using at least one of dimethylformamide, dichloromethane, chloroform, acetone, hexafluoroisopropanol, and ethyl acetate as a solvent, adding L-polylactic acid PLLA and D-polylactic acid PDLA into the solvent respectively, setting a stirring speed of 100 to 500 rpm, and obtaining L-polylactic acid PLLA solution and D-polylactic acid PDLA solution respectively, wherein the mass ratio of L-polylactic acid PLLA to the solvent is 5% to 30%, and the mass ratio of D-polylactic acid PDLA to the solvent is 5% to 30%, mixing the L-polylactic acid PLLA solution and the D-polylactic acid PDLA solution, stirring at a speed of 100 to 500 rpm during mixing, and then freeze-molding at an ultra-low temperature of -150°C to -50°C, and drying at -20°C to -49°C to remove the solvent, to form a stereocomposite crystal SC; The phase transition method comprises: using at least one of dimethylformamide, dichloromethane, chloroform, acetone, hexafluoroisopropanol and ethyl acetate as a solvent, adding L-polylactic acid PLLA and D-polylactic acid PDLA into the solvent respectively, setting the stirring speed to 100-500 rpm, obtaining L-polylactic acid PLLA solution and D-polylactic acid PDLA solution respectively, wherein the mass ratio of L-polylactic acid PLLA to the solvent is 5%-30%, and the mass ratio of D-polylactic acid PDLA to the solvent is 5%-30%, mixing the L-polylactic acid PLLA solution and the D-polylactic acid PDLA solution, stirring the solution at a speed of 100-500 rpm during mixing, then setting the cooling temperature to -20°C to -100°C, and the temperature change rate to 1°C / min to 5°C / min, to form stereocomposite crystals SC.

4. The method according to claim 3, characterized in that In step S2, the proportion of polylactic acid in the polylactic acid solution is 5% to 25%, the mass ratio of the stereocomplex crystal SC to the polylactic acid is 1:20 to 1:2, the solvent used is at least one of dimethylformamide, dichloromethane, chloroform, acetone, hexafluoroisopropanol, and ethyl acetate, the bulking agent is at least one of cellulose acetate, polyvinyl alcohol, polyurethane, polycaprolactone, chitosan and polylactic acid copolymer, and the mass ratio of the bulking agent to the polylactic acid is 1:10 to 2:

1.

5. The method according to claim 4, characterized in that In step S2, when the electrospinning process is adopted, the output voltage of the electrospinning is 5 to 35 kV, the solution consumption rate is 0.5 to 4 mL / h, the spinning and winding speed is 100 to 1500 rpm, the receiving distance is 8 to 30 cm, the spinning temperature is 20 to 50°C, the humidity is 50% to 90%, the average diameter of the polylactic acid fluffy nanofibers is 200 to 990 nm, and the thickness of the polylactic acid fluffy nanofiber membrane is 300 to 1000 μm.

6. The method according to claim 5, characterized in that In step S3, the metal salt is at least one of zinc nitrate (magnesium nitrate, iron nitrate, copper nitrate), zinc acetate (magnesium acetate, iron acetate, copper acetate), zinc sulfate (magnesium sulfate, iron sulfate, copper sulfate), zinc chloride (magnesium chloride, iron chloride, copper chloride), and zinc oxide (magnesium oxide, iron oxide, copper oxide).

7. The method according to claim 6, characterized in that In step S3, the terephthalate reagent is at least one of terephthalic acid, sodium terephthalate, ammonium terephthalate, dimethyl terephthalate, and ammonium hydrogen terephthalate; The imidazole reagent is at least one of methylimidazole, dimethylimidazole, 2-aminobenzimidazole, 2-aminoimidazole, 1-3-aminopropylimidazole, 4-aminoimidazole, and imidazolylbenzene; The solvent is at least one of dimethylsulfamide, dimethylformamide, deionized water, ethanol, methanol, n-butanol, isopropanol, ethylene glycol, and chloroform; The mass ratio of the metal salt to the terephthalate reagent is 1:8-1:1; The mass ratio of the metal salt to the imidazole reagent is 1:10 to 1:1; The mass ratio of the metal salt to the solvent is 1:1000 to 1:50; When stirring, the stirring speed is 100 to 600 rpm and the stirring time is 20 to 40 minutes.

8. The method according to claim 7, characterized in that In step S4, the microwave output power used is 300-1200W, the growth temperature is 150-250°C, the synthesis time is 20-100min, the stirring speed is 10-300rpm, the wavelength range of ultraviolet light UV is 100-400nm, and the irradiation intensity is 100-500mW / cm 2 The irradiation time is the same as the synthesis time, the ultraviolet UV light source is at least one of a mercury lamp, a xenon lamp, an LED UV light source, a black light lamp, an ultraviolet lamp tube, and a nitrogen laser, and the average particle size of the MOF nanocrystals is 100 to 990 nm.

9. The method according to claim 8, characterized in that In step S4, the drying method used is at least one of natural drying, hot air drying, freeze drying, vacuum drying, microwave drying, spray drying, flash drying, and radiation drying.

10. Polylactic acid fluffy nanofiber membrane for efficient gas and particle removal, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • In-situ MOF stereocomplex polylactic acid micro / nano fiber self-powered filter membrane and preparation method thereof

    CN116726729A

  • Polylactic acid fiber filtering membrane as well as preparation method and application thereof

    CN117323845A

  • Apparatus and method for examining a display device

    KR102773497B1

  • Method for producing stereo complex crystals of polylactic acid, polylactic acid, and molded body, synthetic fiber, porous body and ion conductor comprising same

    US20120238652A1